The Thinking Styles in «Songs of Home» of César Vallejo - Fernández Cozman, Camilo (2019)
There is not a single style in a book of poems, book of stories, novel or play. There is a plurality of styles that fight each other. Giovanni Bottiroli, on the basis of Mikhail Bakhtin’s proposal, formulates that there are three styles of thought: separative, that is rigid and suppresses the ambiguities between signifier and meaning; the distinctive, that implies a work with the oppositions and has, sometimes, a dialectic dimension; and the confusive one, that implies the triumph of the chaos in the scope of the discourse. In «Songs of Home», the three styles of thoughts struggle: the separative that is questioned by the distinctive (which implies the dialectical treatment between writing and orality in «The distant steps», for example) and the confusing (that evidences the rupture of the syntax and the embryonic presence of some avant-garde features in «To my brother Miguel», for example).